The european union’s energy security and turkey’s role in the southern gas corridor: Interdependence on the natural gas pipeline between turkey and EU - Tanrıkulu, Faik (Peter Lang AG, 2018)
This study analyses the issue of energy security and natural gas in the Southern Gas Corridor, and its effects on the relationship between the European Union (EU) and Turkey. The increasing consumption of natural gas in the world as an energy source has rendered it a greater strategic importance in the world. Additionally, the conflict between Ukraine, Belarus and Russia over natural gas has threatened both the short and long-term security of the EU’s gas supply. Consequently this conflict has created the necessity to find alternative routes in order to meet Europe’s increasing gas demand. In this context, Turkey’s and the EU’s dependency on Russian natural gas has increased in the last decades, causing both Turkey and the EU to search for outside energy sources. Turkey plays a key role as part of the strategic Southern Gas Corridor initiative, which is a proposed gas pipeline in corporation with the Trans Anatolia Natural Gas Pipeline (TANAP) project, proposed to run from the Caspian region through Turkey to Europe. This study argues that the energy dependency among the countries not only affects the economic decisions, but also the political decisions.
Keywords: Southern Gas Corridor; European Union’s Energy Security; Turkey’s Role